Prevalence of Substance Use Disorders Among African Americans and Caribbean Blacks in the National Survey of American Life - Broman, Clifford L. (American Public Health Association, 2008)
Objectives. We sought to estimate the prevalence of substance disorders for African Americans and Caribbean Blacks in the United States using data from the National Survey of American Life. Methods. A national household probability sample of noninstitutionalized African Americans (n=3570) and Caribbean Blacks (n=1621) was obtained between February 2001 and June 2003 using a slightly modified version of the Composite International Diagnostic Interview. Results. Overall differences in prevalence of substance disorders between the ethnic groups were not significant. Prevalence rates of substance disorders among African Americans exceeded that of Caribbean Blacks among women, those aged 45 to 59 years, and those who were divorced. African Americans in major metropolitan areas had higher prevalence rates, and those in the South had lower ones, compared with those living in other areas. Overall, first-generation Caribbean Blacks were significantly less likely, but second-generation more likely, than were African Americans to meet criteria for overall substance disorders. Conclusions. Failure to distinguish between African Americans and Caribbean Blacks masks important differences in substance use patterns among the Black population in the United States.